An Optimal Control Approach to Malaria Prevention via Insecticide-Treated Nets. (30th July 2013) - Silva, Cristiana J.; Torres, Delfim F. M.
Abstract : Malaria is a life threatening disease, entirely preventable and treatable, provided that the currently recommended interventions are properly implemented. These interventions include vector control through the use of insecticide-treated nets (ITNs). However, ITN possession is not necessarily translated into use. Human behavior change interventions, including information, education, communication (IEC) campaigns and postdistribution hang-up campaigns, are strongly recommended. In this paper, we consider a recent mathematical model for the effects of ITNs on the transmission dynamics of malaria infection, which takes into account the human behavior. We introduce in this model a supervision control, representing IEC campaigns for improving the ITN usage. We propose and solve an optimal control problem where the aim is to minimize the number of infected humans while keeping the cost as low as possible. Numerical results are provided, which show the effectiveness of the optimal control interventions.